Old Mother Middle Muddle - Martin, Bill, 1916-; Madden, Donald B. (New York, Holt, Rinehart and Winston, 1970)
Old Mother Middle Muddle's decision to make a cup of tea sends a wave of anticipation through the barnyard.
Keywords: Animals -- Fiction